RANCANG BANGUN SISTEM PENGENDALIAN ON/OFF PADA MESIN FAN DI AREA PRODUKSI DI PT PEGATRON - Sitindaon, Putra Januara; Sirait, Ganda (Computer Science and Industrial Engineering, 2023)
ABSTRACT The workers at PT Pegatron experience the constraints in turning on and turning off the fan machine, which often disrupts their work because turning on and turning off the fan machine requires division facilities to turn it on, so a lot of time is wasted and the workforce is inefficient. Based on this, the researcher intends to conduct research on the design of the on/off button for this fan engine using Design for Manufacture and Assembly (DFMA). This study aims to make a design and compare between the initial design and design alternative designs based on the evaluation results on the initial design using DFMA and the basis for making parameters so that the best design choice can be determined. Based on the initial design DFMA analysis, it was found that the material for the fan engine is a total of 58 components, an estimated cost of IDR 15,420,500. the time needed to turn on the fan engine is between 7 minutes – 8 minutes. The costs incurred for electricity from the initial design amounted to 152 million – 160 million. From the results of the evaluation of the initial fan engine design, an alternative fan engine design was obtained. Alternative designs that were designed entirely were analyzed using DFMA and the results obtained for the components making up the fan machine totaled 87 components with a total assembly time of 18 hours and a total cost of Rp. 16,285,000 and a new design electricity cost of 120 million and the time to turn on the fan engine is 2 sec.